PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP KETERAMPILAN KOLABORASI SISWA PADA PEMBELAJARAN IPAS DI KELAS V SD NEGERI 2 MATA IE - Khaira; Tursinawati; Mislinawati (STKIP Subang, 2026)
This study was motivated by the low level of collaboration skills among fifth-grade students in Science and Social Studies (IPAS) learning at SD Negeri 2 Mata Ie. The study aimed to describe the implementation of the Teams Games Tournament (TGT) cooperative learning model and students' collaboration skills during the learning process. This research employed a descriptive qualitative approach. The participants consisted of one fifth-grade teacher and 20 fifth-grade students. Data were collected through classroom observations and structured interviews with the teacher. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Teams Games Tournament (TGT) learning model was carried out through five stages, namely class presentation, team study, games, tournaments, and team recognition. The implementation of these stages encouraged students to participate actively in group activities and facilitated the development of collaboration skills. Students' collaboration skills were categorized as good to very good. The indicators of mutual respect (3.35) and responsibility (3.30) were categorized as very good, while active contribution (3.20), productive work (3.20), and flexibility and compromise (3.15) were categorized as good. Therefore, the Teams Games Tournament (TGT) cooperative learning model can support the development of collaboration skills in IPAS learning.